Phytochemical studies, antimicrobial and antituberculosis evaluation of extracts from the stem bark of Psorospermum senegalense(Spach) - H, Momoh,; M.B, Dambata,; M.T, Tahir, (IJRDO-Journal of Applied Science, 2017)
Psorospermum senegalense which is traditionally used in the treatment of tuberclosis (TB) inNorthern Nigeria was investigated. Phytochemical analysis revealed the presence of flavonoids,carbohydrates, cardiac glycosides, steroids, triterpenes, alkaloids, tannins and saponins.Preliminary antimicrobial studies, showed that the ethyl acetate (EA) extract showed the highestzone of inhibition (ZI) ranging from 25 to 31 mm on the test organism. The hexane (HE),dichloromethane (DCM) and methanol extract showed ZI ranging from 18-21, 20- 27 and 20-24mm on the test organism respectively. The results of the minimum inhibitory concentration(MIC) determination shows that EA inhibited all the test organism at a low concentration of 7.5mg/mL except for Pseudomonas aeruginosa (PA) and Candida albican (CA) which showed anMIC of 15 mg/mL. On Mycobacterium bovis (BCG) an MIC of 2.5 mg/mL was observed forEA, while other extracts did not show activity.